SELECTIVITY OF HYDRAZINE DEHYDROGENATION REACTION ON NICKEL(111) SURFACE AS ANODE CATALYST OF DIRECT HYDRAZINE FUEL CELL - IRFANDI - GEWINNER S. C. (NIM : 13313050)- SENDERANTO SINAGA, MUHAMMAD
Direct Hydrazine Fuel Cell generates electricity through hydrazine dehydrogenation reaction which forms water. Furthermore, it also forms ammonia. Ammonia is an unwanted reaction product because it can poison the catalyst. Nickel is one of the non-noble metal catalysts having high catalytic activity. Regarding direct hydrazine fuel cells, studies on selectivity between water-forming reaction and ammonia-forming reaction are required in order to design better catalysts. Selectivity is investigated by calculating activation energies of both reactions. Calculation result shows that activation energy of water-forming reaction is 0.28 eV and ammonia-forming reaction is 0.33 eV. Activation energy consists of contribution due to structural deformation, adsorption strength of each adsorbate, and adsorbate-adsorbate interaction. Contribution due to structural deformation and adsorption of each adsorbate on water-forming reaction is lower than ammonia-forming reaction, which is 2.37 eV compared to 2.93 eV. Meanwhile, adsorbaate-adsorbate interaction energy on water-forming reaction (𝑁𝑖−𝑂𝐻−𝑁2𝐻4) is -2.08 eV and ammonia-forming reaction (𝑁𝑖−𝑁𝐻2−𝑁2𝐻4) is -2.60 eV. This interaction strength is proportional to the amount of charge depletion occurring in hydrogen atom of hydrazine which is closest to 𝑂𝐻 or 𝑁𝐻2.